A novel multiscale and multipath convolutional neural network based age-related macular degeneration detection using OCT images. (September 2021) - Thomas, Anju; Harikrishnan, P.M.; Ramachandran, Rajiv; Ramachandran, Srikkanth; Manoj, Rigved; Palanisamy, P.; Gopi, Varun P.
Highlights: The proposed CNN consist of multiscale and multipath Convolutional Layers (CL). The multiscale CL allows the network to generate more local structures with different filter sizes. The multipath feature extraction permits CNN to merge more features regarding the sparse local and fine global structures. The 16 relevant features from the second fully connected layer of the CNN are fed into the classifier reduces the computation time of classification. Suitable for real-time implementation due to the use of only 6 CL which reduces the complexity and learnable parameters. Abstract: Background and Objective: One of the significant retinal diseases that affected older people is called Age-related Macular Degeneration (AMD). The first stage creates a blur effect on vision and later leads to central vision loss. Most people overlooked the primary stage blurring and converted it into an advanced stage. There is no proper treatment to cure the disease. So the early detection of AMD is essential to prevent its extension into the advanced stage. This paper proposes a novel deep Convolutional Neural Network (CNN) architecture to automate AMD diagnosis early from Optical Coherence Tomographic (OCT) images. Methods: The proposed architecture is a multiscale and multipath CNN with six convolutional layers. The multiscale convolution layer permits the network to produce many local structures with various filter dimensions. The multipath feature extraction permits CNN to merge more features regarding the sparse local and fine global structures. The performance of the proposed architecture is evaluated through ten-fold cross-validation methods using different classifiers like support vector machine, multi-layer perceptron, and random forest. Results: The proposed CNN with the random forest classifier gives the best classification accuracy results. The proposed method is tested on data set 1, data set 2, data set 3, data set 4, and achieved an accuracy of 0.9666, 0.9897, 0.9974, and 0.9978 respectively, with random forest classifier. Also, we tested the combination of first three data sets and achieved an accuracy of 0.9902. Conclusions: An efficient algorithm for detecting AMD from OCT images is proposed based on a multiscale and multipath CNN architecture. Comparison with other approaches produced results that exhibit the efficiency of the proposed algorithm in the detection of AMD. The proposed architecture can be applied in rapid screening of the eye for the early detection of AMD. Due to less complexity and fewer learnable parameters.